Engajamento e efeito de monologismo no gênero notícia de popularização científica - Scherer, Anelise Scotti (2013)
Science popularization (SP) involves a complex process of recontextualization of scientific knowledge in the mass media. This process is realized in discursive genres through which the journalist mediator appropriates and re-elaborates the knowledge produced by specialists to a non-specialized audience (MOTTA-ROTH, 2009), making use of intertextual strategies. One of the SP genres investigated in the umbrella project Análise crítica de gêneros discursivos em práticas sociais de popularização da ciência (MOTTA-ROTH, 2010a), developed at Laboratório de Pesquisa e Ensino de Leitura e Redação (LABLER), under supervision of Professor Désirée Motta Roth, is the SP news genre. Partindo desses resultados obtidos sob a ótica da Análise Crítica de Gênero (MEURER, 2002; BHATIA, 2004; MOTTA-ROTH, 2005; 2008), o objetivo deste estudo é investigar os expoentes linguísticos da intertextualidade que evidenciam o jogo entre expansão e contração dialógica em 45 notícias de PC em inglês.The results of analyses concerning this genre and related to the umbrella project have pointed to a predominance of the researcher s voice as the voice of science (MARCUZZO, 2011) and, as a consequence, to an effect of monologism (MOTTA-ROTH; LOVATO, 2011, based on MOIRAND, 2003), which results from and reinforces the hegemonic discourse of science. Based on these results obtained under the perspective of Critical Genre Analysis (MEURER, 2002; BHATIA, 2004; MOTTA-ROTH, 2005; 2008), the objective of this study is to investigate the linguistic exponents of Engagement that serve as evidence of the relation between dialogic contraction and expansion in 45 SP news texts in English. Therefore, the present study has two focus of analysis: text and context. The context analysis involves: a) investigating the process of SP; and b) investigating the sites of the publications in terms of the variables field, tenor and mode. The text analysis involves: a) identifying quoting and reporting (projection); b) interpreting the linguistic traces of engagement (acknowledge, distance and endorse) in the texts of the corpus and c) relating data from text and context analyses. The results corroborate the effect of monologism identified by Motta-Roth and Lovato (2011) as they indicate that, in spite of the higher recurrence of dialogic expansion (mainly ackowledge), the journalist promotes nor the coexistence neither the debate among the different voices than the journalist s. These results suggest that, besides positioning him/herself as the information mediator, the journalist author of the news contracts the discourse as he/she emphasizes the specialist s voice and restrains the participation of other sectors of society among the comments about the popularized research (MARCUZZO, 2011), reinforcing the hegemonic power of science in society.